Nomenclator, geographic and stratigraphic distribution of the family Triphoridae (Mollusca: Gastropoda) - Bakker, Piet A.j.; Albano, Paolo G. (Zootaxa, 2022)
The microgastropod family Triphoridae is one of the five most diverse marine molluscan families. It likely hosts a few thousand species worldwide, but its taxonomy has long been considered challenging due to the high diversity and subtle morphological characters needed for species delimitation. Consequently, only a small portion of the species appears to be formally described to date. However, further taxonomic work should be based on robust knowledge on the numerous names introduced so far. In this perspective, we have here compiled a list of all published names that can be attributed to the fossil and extant Triphoridae. We list 958 species and 75 genus names, of which 771 are known as extant species and 146 as fossil species, 41 are known from both fossil and extant records. We provide information on type locality and horizon, type material, synonymy and homonymy. Importantly, based on the review of hundreds of publications, we provide a preliminary overview of the geographic and stratigraphic distribution.